ANALISIS BEBAN TAKSEIMBANG TERHADAP RUGI-RUGI DAYA DAN EFISIENSI TRANSFORMATOR KL0005 JARINGAN DISTRIBUSI SEKUNDER PADA PENYULANG KLUNGKUNG - I Putu Gede Kartika; I Ketut Wijaya; I Made Mataram (Program Studi Teknik Elektro UNUD, 2018)
Load imbalance will always occur in low voltage network systems (JTR), this is due to the uneven use of one phase load on customers coming from household elektrical appliances. The uneven use of loads will cause power losses in the network and drop in voltage. Load equalization on the network is one way to reduce power losses and voltage drop. This research was conducted by analyzing power losses and unbalanced load voltage drop and balanced load on the KL0005 transformer secondary distribution network on the Klungkung Feeder. Based on the result of the analysis, the power losses in the unbalanced load state obtained a result of 3.029 kW and the voltage drop in phase R was 6,1%, phase S was 3,5% and phase T was 0%, while the result of the power loss analysis balanced load obtained 2,9 kW and voltage drop in phase R is 2,6%, phasa S is 1,3% and phase T is 3% with difference in balanced load efficiency and unbalance load of 0,1%.